Quantitation of cytidine‐5′‐monophospho‐N‐acetylneuraminic acid in human leukocytes using LC–MS/MS: method development and validation. (8th January 2020) - Fang, Meng; Xu, Xin; Zhang, Michael; Shi, Yifan; Gu, Guodong; Liu, Wanjing; Class, Bradley; Ciccone, Carla; Gahl, William A.; Huizing, Marjan; Carrillo, Nuria; Wang, Amy Q.
Abstract: The biosynthesis of sialic acid (Neu5Ac) leads to the intracellular production of cytidine‐5′‐monophospho ‐N‐ acetylneuraminic acid (CMP‐Neu5Ac), the active sialic acid donor to nascent glycans (glycoproteins and glycolipids) in the Golgi. UDP ‐N‐ acetylglucosamine 2‐epimerase/ N ‐acetylmannosamine kinase myopathy is a rare autosomal recessive muscular disease characterized by progressive muscle weakness and atrophy. To quantify the intracellular levels of CMP‐Neu5Ac as well as N ‐acetylmannosamine (ManNAc) and Neu5Ac in human leukocytes, we developed and validated robust liquid chromatography–tandem mass spectrometry methods. A fit‐for‐purpose approach was implemented for method validation. Hydrophilic interaction chromatography was used to retain three hydrophilic analytes. The human leukocyte pellets were lysed and extracted in a methanol–water mixture and the leukocyte extract was used for LC–MS/MS analysis. The lower limits of quantitation for ManNAc, Neu5Ac and CMP‐Neu5Ac were 25.0, 25.0 and 10.0 ng/ml, respectively. These validated methods were applied to a clinical study.